Distinct role of the right temporoparietal junction in advantageous and disadvantageous inequity: A tDCS study - Wu, Shijing; Cai, Shenggang; Dong, Zhiqiang; Zhang, Hanqi (Frontiers in Behavioral Neuroscience, 2023)
Fairness is a hallmark of humans’ ability to maintain cooperative relationships with large numbers of unrelated others. It influences many aspects of daily life, from how people share their resources with partners to how policymakers shape income distribution policy. The right temporoparietal junction (rTPJ) is a hub of the mentalizing network and it has been proposed to play a key role in guiding human reciprocal behavior; however, its precise functional contribution to fair behavior in situations of advantageous and disadvantageous inequity remains unclear. The purpose of this study was to clarify the role of the rTPJ in relation to fair behavior in situations of advantageous and disadvantageous inequity by modulating the activation of the rTPJ through transcranial direct current stimulation (tDCS). Anodal tDCS at 1.5 mA over the primary visual cortex (VC) or rTPJ was performed and participants subsequently played a binary-choice version of the Dictator Game. We found that anodal tDCS over the rTPJ increased the participants’ equity choices in the disadvantageous inequity situation, but not in the advantageous inequity situation. The tDCS effect is moderated by sex, and in particular the tDCS effect increases female equity choices. The results suggest that the rTPJ plays a distinct role in inequity aversion in these two types of inequity situations.